Efficacy and safety analysis of TACE + PEI + lenvatinib compared with TACE + lenvatinib for the treatment of hepatocellular carcinoma with PVTT: a retrospective study - Lu, Haohao; Zheng, Chuansheng; Liang, Bin; Xia, Xiangwen; Fan, Hongjie (Frontiers in Oncology, 2024)
The aim of this study was to investigate the efficacy and safety of transcatheter arterial chemoembolization (TACE) combined with percutaneous ethanol injection (PEI) and lenvatinib in HCC patients with PVTT (Vp2-3), thus providing a safe and effective treatment strategy for advanced HCC patients.Clinical data of 227 patients with unresectable HCC and PVTT treated at the Union Hospital from January 2018 to December 2021 were retrospectively analyzed. The patients were divided into two groups according to their treatment methods: TACE+PEI+lenvatinib group (N=103) and TACE+lenvatinib group (N=124).The proportion of patients with disappearance, shrinkage, or no change of PVTT after treatment was significantly higher in the TACE+PEI+lenvatinib group compared to the TACE+lenvatinib group, with statistical significance (P<0.001). The TACE+PEI+lenvatinib group had higher objective response rate (ORR) (50.5% vs. 25.8%, P<0.001) and disease control rate (DCR) (87.4% vs. 74.2%, P=0.013) than the TACE+lenvatinib group. The median progression-free survival (mPFS) of the TACE+PEI+lenvatinib group was longer than that of the TACE+lenvatinib group (8.1 months vs. 6.5 months, P<0.001). Consistently, the median overall survival (mOS) of the TACE+PEI+lenvatinib group was longer than that of the TACE+lenvatinib group (17.1 months vs. 13.9 months, P<0.001).Among HCC patients with PVTT (Vp2-3), TACE+PEI+lenvatinib is more effective comparing to TACE+lenvatinib in prolonging PFS and OS. The control of PVTT in the TACE+PEI+lenvatinib group was significantly more satisfactory than that in the TACE+lenvatinib group. TACE+PEI+lenvatinib is a safe and effective treatment strategy for HCC patients with PVTT (Vp2-3).